PENGARUH SUMBER DAYA MANUSIA, TEKNOLOGI INFORMASI, GOOD CORPORATE GOVERNANCE , DAN MANAJEMEN RISIKO TERHADAP KINERJA KEUANGAN DI MASA PANDEMI COVID-19 PADA BMT DI KABUPATEN TULUNGAGUNG - Sapta Sri Maharani; Dyah Dyah Pravitasari (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
The impact that occurred due to the covid-19 pandemic in the midst of the economic difficulties allowed the occurrence of payment jams or arrears to customers at BMT, so this study aims to examine the influence of Human Resources, information technology, GCG, and risk management on financial performance during the covid-19 pandemic so that financial performance continues to run smoothly. The population of this study was BMT in Tulungagung Regency. This study used samples from the population in 3 BMTs in Tulungagung which were used as samples, namely BMT Muamalah, BMT Istiqomah, BMT Pahlawan. The sampling technique used is purposive sampling. The sample in this study were all staff/employees at the three BMTs in Tulungagung district. The results of the study indicate that human resources are needed in a financial performance. By having a clear understanding of roles and functions. Good financial performance will make a positive contribution to BMT in Tulungagung Regency